Determinants of Mental Health Literacy Among Correctional Officers - Alwi, Puspita; Ayubi, Dian (Universitas Airlangga, 2024)
Background: Inmates are at higher risk of developing mental problems. Correctional officers have an important role in supporting inmate's mental health. Correctional officers' insufficient understanding of mental health can contribute to adverse outcomes for mentally ill inmates in the criminal justice system. Aims: This study aimed to determine factors associated with correctional officers's mental health literacy. Methods: This is quantitative research using a cross-sectional approach. This research used secondary data from a study about Correctional Officer's Perceptions towards Mental Health, which was conducted in June 2023. The population was 1564 officers in Central Java. The independent variable was demographic factors, history of seminar/training about mental health, and previous contact with someone who has a mental health problem. The dependent variable was mental health literacy, measured with the Mental Health Knowledge Questionnaire (MHKQ). Data was analyzed bivariate with a chi-square test. Results: About 66% of correctional institution officers had low mental health literacy. The status as a healthcare worker (p=0.01), longer working duration (p=0.03), experience of attending mental health seminars (p=0.00), and contact with someone that has mental health problem (p=0.03) have a significant correlation with officer level of mental health literacy. Conclusion: Correctional officers often have limited mental health knowledge. Level of experience, job scope, contact experience with someone with a mental health problem, and mental health training positively impact their literacy. Increasing mental health education in correctional facilities is vital to enhance this, focusing on risk factors and care delivery.